1986
DOI: 10.1055/s-2007-1018408
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Neodymium-YAG Laser Treatment of Obstructive Colon Cancer

Abstract: Present conventional surgical therapy of obstructive colon cancers of the right colon is primary resection, whereas in the left colon it is a two-stage or three-stage operation with a temporary colostomy. Morbidity and mortality rates in staged operations are still as high as 40% and 24%, respectively. Preoperative recanalization of obstructive cancers by neodymium-YAG laser vaporization will tend to relieve the symptoms of ileus and will permit preoperative peroral bowel lavage. For this reason primary resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Recently, laser recanalization and luminal stenting have been used to temporarily relieve bowel obstruction and facilitate bowel preparation, resection, and primary anastomosis. Preoperative recanalization of obstructive colorectal cancers with a neodymium‐YAG laser and subsequent resection and anastomosis was performed with a 3.7 % mortality rate (8). A similar approach with stent placement allows for a one‐stage procedure in 60 % – 92 % of patients (20).…”
Section: Specific Management Issuesmentioning
confidence: 99%
“…Recently, laser recanalization and luminal stenting have been used to temporarily relieve bowel obstruction and facilitate bowel preparation, resection, and primary anastomosis. Preoperative recanalization of obstructive colorectal cancers with a neodymium‐YAG laser and subsequent resection and anastomosis was performed with a 3.7 % mortality rate (8). A similar approach with stent placement allows for a one‐stage procedure in 60 % – 92 % of patients (20).…”
Section: Specific Management Issuesmentioning
confidence: 99%
“…The neodymium yttrium aluminum garnet (Nd:YAG) laser has been effective in these cases because it has both vaporizing and coagulating properties. The laser can achieve recanalization of an obstructing rectal tumor to allow preoperative bowel preparation before definitive resection [54,55]. Palliation can be achieved in patients who are not surgical candidates or have widespread metastatic disease, maintaining a patent lumen and avoiding a colostomy.…”
Section: Laser Treatmentmentioning
confidence: 99%
“…Kiefhaber et al [48] reported on the results of preoperative recanalization of obstructive cancers by Nd:YAG laser vaporization in 57 patients. The goal of laser recanalization was to permit preoperative orthograde colon lavage and a subsequent primary resection, without a temporary colostomy.…”
Section: Applications In the Lower G-i Tractmentioning
confidence: 99%